Effect of Predry-treatment on the bioactive constituents and quality of avocado (Persea americana Mill.) oil from three cultivars growing in China - Wang, Jiashui; Yang, Hongbin; Wu, Peicong; Zhang, Jiali; Ma, Weihong; Li, Yanxia; Liu, Jinping (Frontiers in Nutrition, 2023)
We would like to submit the enclosed manuscript entitled "Effect of Predry-treatment on the Bioactive Constituents and Quality of Avocado (Persea americana Mill.) Oil from Three Cultivars Growing in China" to be considered for publication in "Frontiers in Nutrition" as an original research article.We believe this manuscript meets the scope of this journal because it concerns the utilization of avocado pulp to produce functional oil that may be applied in food or cosmetic industry. The effect of avocado variety and predry-treatments on the quality and bioactive constituents of avocado oil was investigated. Specifically, oil was extracted from three main Chinese avocado varieties (Hass, Pinkerton and Reed) whose pulp was subjected to three different drying treatments (oven, vacuum and freeze drying). The physiochemical properties and quality of the oil were evaluated. Both avocado variety and predry-treatment significantly influenced the final quality and bioactive compounds composition of the oil. Importantly, we found that the combination of Hass variety and freeze drying can produce avocado oil with high yield and good quality indices like fatty acid composition, solid fat content, peroxide value, anisidine value and etc. The results obtained in this study can help lay the foundation of future exploitation of Hass avocado as a better choice for producing avocado oil with better nutritional and functional properties.